The context and consequences of 2024 early parliamentary election in France: the rise of actors from the right and left spectrum of political action - Perišić, Nikola (Napredak, 2025)
After the poor electoral result of his political option in the European Parliament elections, President of France Emmanuel Macron decided to call an early parliamentary election. This move is unusual in the functioning of the French political system because early parliamentary elections are quite rare in this country. The voters’ dissatisfaction with various decisions of Macron during his two presidential mandates were used by the political options from the right and left spectrum of political action for increasing their own rating. However, owing to the electoral system and post-electoral calculations, the political movement led by Macron kept a sort of political power in the Parliament; namely, the opposition actors are not able to form the majority that would lead to cohabitation, which has not been recorded since 2000, when the shortening of the presidential mandate from seven to five years led to the merging of presidential and parliamentary elections in the same year. Such calling of early parliamentary elections, in case they are held at their regular time in the future, separates elections while increasing the possibility of cohabitation being established in the forthcoming period. This paper will analyze and explore the manner in which the French political system will function in that situation, as well as the direction in which further growth of political options on the right and left spectrum.